2021
DOI: 10.1016/j.matpr.2020.04.671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nickel-based laser coatings on phase composition and corrosion behaviour of titanium alloy for offshore application

Abstract: Recent advances in titanium alloy applications in the offshore industry have been realized through the development of laser surface modification technique. The distinctive outcome of this technique has provided increase in the utilization of titanium in offshore drilling risers for special drilling operations and various subsea and tubing applications. In this work, surface mitigation and corrosion degradation of titanium alloy in aggressive sulfuric acid were investigated using electrochemical technique (line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…They indicated that the use of an interlayer that acts as a transition material could significantly reduce these reported cracks. Adesina et al [125], in agreement with Pardal et al [126], elucidated further that such intermetallics and reactive oxides experienced during deposition can influence the corrosion behaviour of coatings and even hinder the joining of materials. On the other hand, it is worth noting that some intermetallics have good properties such as NiTi intermetallics having good corrosion resistance, wear, and oxidation resistance [127].…”
Section: Boilersmentioning
confidence: 57%
“…They indicated that the use of an interlayer that acts as a transition material could significantly reduce these reported cracks. Adesina et al [125], in agreement with Pardal et al [126], elucidated further that such intermetallics and reactive oxides experienced during deposition can influence the corrosion behaviour of coatings and even hinder the joining of materials. On the other hand, it is worth noting that some intermetallics have good properties such as NiTi intermetallics having good corrosion resistance, wear, and oxidation resistance [127].…”
Section: Boilersmentioning
confidence: 57%
“…Nickel-based alloy coatings are widely used in marine, chemical, nuclear industry and machinery fields owing to their toughness, strong oxidation resistance and high corrosion resistance [8]. Given the rapid development of industrialization and the complicated operating environment, it is important that the wear resistance of the coatings, especially for the service life of minerals machinery, is developed further.…”
Section: Introductionmentioning
confidence: 99%